Respuesta :
Answer:
[tex](\frac{3}{2},102)[/tex]
Step-by-step explanation:
Given
[tex]f(x)=88x^2-264x+300[/tex] --- Missing from the question
Required
The symmetry
First, we express f(x) as: [tex]f(x) = a(x - h)^2 + k[/tex]
Where the symmetry is: (h, y) and x = h
Equate f(x) to 0
[tex]88x^2-264x+300 = 0[/tex]
Subtract 300 from both sides
[tex]88x^2-264x+300 - 300= 0 - 300[/tex]
[tex]88x^2 - 264x= - 300[/tex]
Factorize
[tex]88(x^2 - 3x) = -300[/tex]
On the left-hand side, the coefficient of x is -3.
Divide by 2 and add the square to both sides.
So, we have:
[tex]88(x^2 - 3x) + (\frac{3}{2})^2 = -300 + (\frac{3}{2})^2[/tex]
Multiply the new terms by 88 (to make it factorizable)
[tex]88(x^2 - 3x ) +88* (\frac{3}{2})^2 = -300 + 88 * (\frac{3}{2})^2[/tex]
Factorize
[tex]88(x^2 - 3x + (\frac{3}{2})^2) = -300 + 88 * (\frac{3}{2})^2[/tex]
The quadratic expression in the bracket is a perfect square. This gives:
[tex]88(x - \frac{3}{2})^2 = -300 + 88 * (\frac{3}{2})^2[/tex]
[tex]88(x - \frac{3}{2})^2 = -300 + 88 * \frac{9}{4}[/tex]
[tex]88(x - \frac{3}{2})^2 = -300 + 22 * 9[/tex]
[tex]88(x - \frac{3}{2})^2 = -102[/tex]
Add 102 to both sides
[tex]88(x - \frac{3}{2})^2 +102= -102 + 102[/tex]
[tex]88(x - \frac{3}{2})^2 +102= 0[/tex]
Equate to y
[tex]y = 88(x - \frac{3}{2})^2 +102[/tex]
Recall that:
The symmetry is: (h, y)
By comparison with [tex]f(x) = a(x - h)^2 + k[/tex] and x = h
[tex]h = \frac{3}{2}[/tex]
So: [tex]x = \frac{3}{2}[/tex]
Substitute [tex]x = \frac{3}{2}[/tex] in [tex]y = 88(x - \frac{3}{2})^2 +102[/tex]
[tex]y = 88(\frac{3}{2} - \frac{3}{2})^2 +102[/tex]
[tex]y = 88(0)^2 +102[/tex]
[tex]y = 0 +102[/tex]
[tex]y = 102[/tex]
So, the symmetry is: [tex](\frac{3}{2},102)[/tex]